Intercultural sensitivity among nursing students: a latent profile analysis - You-Ran Liu; Yan Wang; Tengfei Liang; Shumei Zhuang; Xi Wang; Jie Wang; Hui Xie (BMC Nursing)
Abstract Background Cultivating intercultural sensitivity is essential for achieving cultural competence. To provide quality nursing care, nurses must be aware of cultural factors, understand cultural differences, and demonstrate intercultural sensitivity. The status and influencing factors of intercultural sensitivity among nursing students are equally important and should not be overlooked. Previous studies on nursing students’ intercultural sensitivity have primarily focused on the overall level and its influencing factors, while neglecting heterogeneity in intercultural sensitivity. Therefore, this study aims to investigate the potential types of intercultural sensitivity and related variables among nursing students. Methods A total of 599 nursing students (mean age:20.24, 439 female) from Anhui Province, China, were recruited. Demographic information and intercultural sensitivity of nursing students were collected through an online survey using the " Questionnaire Star " website. The Intercultural Sensitivity Scale was employed to assess intercultural sensitivity. Latent profile analysis was performed to classify nursing students’ levels of intercultural sensitivity, and logistic regression was used to explore factors influencing different latent classes of intercultural sensitivity. Results Nursing students’ intercultural sensitivity was divided into three latent profiles: the “high intercultural sensitivity-moderate interaction enjoyment group” (N = 164), the “moderate intercultural sensitivity-low interaction enjoyment group” (N = 262), and the “low intercultural sensitivity-high interaction enjoyment group” (N = 173). Gender, grade, experience of international exchange, and English level were identified as influencing factors for the nursing students’ latent classes of intercultural sensitivity. Conclusions Nursing students demonstrated significant heterogeneity in intercultural sensitivity. Educators can identify the characteristics and influencing factors of each profile early on to provide tailored support strategies, thereby helping to improve students’ intercultural sensitivity. Clinical trial number Not applicable.